Evaluation of a novel restorative protocol to treat non-carious cervical lesion associated with gingival recession: a 2-year follow-up randomized clinical trial - Mathias-Santamaria, Ingrid Fernandes [UNESP]; Santamaria, Mauro Pedrine [UNESP]; Silveira, Camila Augusto [UNESP]; Martinho, Frederico Canato; de Melo, Mary Anne Sampaio; De Marco, Andrea Carvalho [UNESP]; Augusto, Marina Gullo; de Andrade, Guilherme Schmitt; Roulet, Jean-François; Bresciani, Eduardo [UNESP] (Springer Nature, 2023)
Objective: To compare 2 different resin composites and 2 adhesive systems used in a new restorative protocol (partial restoration) to treat non-carious cervical lesions associated with gingival recession type 1 (RT1). Material and methods: Eighty combined defects (CDs) were treated with a partial restoration and periodontal plastic surgery for root coverage. The CDs were randomly assigned to one of the following groups: NP + TE (n = 20), nanofilled composite and 2-step total-etch adhesive system; NP + UA (n = 20), nanofilled composite and universal adhesive system; MH + TE (n = 20), microhybrid composite and 2-step total-etch adhesive; MH + UA (n = 20), microhybrid composite and universal adhesive. Restorations were assessed using the United States Public Health Service (USPHS) criteria at 1 week (baseline) and 6, 12, and 24 months. Survival rate, periodontal parameters, dentin hypersensitivity (DH), and aesthetics were also evaluated. Results: After 24 months, only the MH + TE group did not lose any restoration, with no significant differences between groups. For surface roughness parameter, MH presented 83.3% of the restorations scoring Bravo, whereas NP presented 48.5% of the restorations scoring Bravo. All groups presented restorations with marginal discoloration. All periodontal parameters behaved similarly, regardless of the restorative material. All groups presented significant reductions of dentin hypersensitivity and improved aesthetic perceptions (p < 0.05). Conclusion: Both resin composites and adhesives tested can be combined for partial restorations to treat CDs. Clinical relevance: This new restorative-surgical protocol to treat CDs presents satisfactory outcomes. The partial restorations can be successfully executed with both combinations of adhesives and resin composites evaluated in this investigation. TRN: ClinicalTrial.gov: NCT03215615; registration date July 12, 2017.
Keywords: Composite resin; Dental restoration wear; Gingival recession; Tooth cervix; Tooth wear